Role of cardiac rehabilitation in patient with pulmonary hypertension on functional capacity and quality of life - Simamora, Ronaldo; Chandra, Christian Rendy; Ambrari, Ade Meidian; Sukmawan, Renan (Indian Journal of Case Reports, 2022)
Patients with pulmonary hypertension (PH) continue to develop significant exertional symptoms and reduced quality of life despite receiving pharmacological therapy. Guidelines highlighted the importance of rehabilitation as part of management in PH. However, the cardiac rehabilitation program is still underused. We present a case of functional capacity improvement in patients with surgically corrected secundum atrial septal defect (ASD) with PH who underwent cardiac rehabilitation program. A 30-year-old female with a previous history of surgically corrected ASD went to our rehabilitation program in our hospital. She had a 3-weeks program of rehabilitation, and there were improvements in symptoms, clinical parameters, and quality of life after completion of the cardiac rehabilitation program. Rehabilitation can be an adjuvant for pharmacological therapy for PH that has been proven to improve the quality of life in patients with PH